A Church in Filadelfia, Costa Rica - Jae Cha (Oz, 2006)
This project is being built in Filadelfia, Costa Rica, a northern town near Liberia. The site is in a residential neighborhood that has “permanent” houses. In order to try to build within that context, we proposed a church building that used local concrete and wood similar to the existing houses.